Experience of acute ascending aortic dissection treatment - Boiko, V. V.; Buchnieva, O. V.; Shafer, Y. V.; Pisklova, Y. V.; Bogun, Y. V.; Krylova, O. S. (Ukrainian Journal of Cardiovascular Surgery, 2018)
Acute aortic dissection, type A, is a demanding issue in cardiac surgery. Since the first attempts of surgical treatment among patients with acute aortic dissection in 1955(DeBakey) more than sixty years has passed. The article describes the features of surgical treatment among patients with acute aortic dissection without circulatory arrest between years 2012 and 2018 in ST “Zaycev V. T. Institute of General and Urgent Surgery AMS of Ukraine”.